2017
DOI: 10.17645/si.v5i2.917
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking and Syrian Refugee Smuggling: Evidence from the Balkan Route

Abstract: As of March 2016, 4.8 million Syrian refugees were scattered in two dozen countries by the civil war. Refugee smuggling has been a major catalyst of human trafficking in the Middle East and Europe migrant crises. Data on the extent to which smuggling devolved into trafficking in this refugee wave is, however, scarce. This article investigates how Syrian refugees interact with smugglers, shedding light on how human smuggling and human trafficking interrelated on the Balkan Route. I rely on original evidence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 13 publications
1
45
0
2
Order By: Relevance
“…We suggest, in other words, that the agency of mid‐level actors pressures migrant agency in counter‐intuitive ways (see also Mandic, ). In doing so, we do not exonerate law‐breakers or reckless risk‐takers from responsibility, we merely observe some of the conditions under which such decision‐making occurs.…”
Section: The Risks Of Migrant Smugglingmentioning
confidence: 88%
“…We suggest, in other words, that the agency of mid‐level actors pressures migrant agency in counter‐intuitive ways (see also Mandic, ). In doing so, we do not exonerate law‐breakers or reckless risk‐takers from responsibility, we merely observe some of the conditions under which such decision‐making occurs.…”
Section: The Risks Of Migrant Smugglingmentioning
confidence: 88%
“…One social worker described how migrants/refugees were often under some pressure from family and community members as well who had as a personal goal to resettle in the EU. One study found that a sizable proportion of Syrian refugees along the Balkan route were following family or friends who had previously travelled the route (serving as Btrailblazers^) and had a set destination [29]. The unpredictability and rapid changes of border and migration management may also enhance the urgency to move on, for fear of being trapped within closed or closing borders.…”
Section: Discussion: Barriers In Identifying Trafficked Migrants and mentioning
confidence: 99%
“…The focus of the debate about smuggling versus trafficking in Mediterranean boat crossings has been on how those who transport people across borders are to be understoodas smugglers or as traffickers. One recent study of trafficking and smuggling along the Balkan route found that, while the overwhelming majority of migrants/refugees (∼75%) did not report trafficking experiences, 7.9% of the sample reported engaging in labor during migration; 26.8% of the sample reported experiencing deception at the hands of smugglers; and 12.2% of the sample reported involuntary family separations caused by smugglers [29]. However, while smugglers were involved in some human trafficking cases identified in Serbia, this far from covered all human trafficking cases.…”
Section: Experiences With Identification: Grey Areas and Conceptual Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of scholarly interest in these topics continues to grow, and in this issue the authors explore some of the most pressing manifestations of human trafficking around the world. Articles by Ventrella (2017) and by Mandić (2017) explore the highly topical issue of the confluence of smuggling and human trafficking in the context of distress migration from northern Africa and the Middle East into the European Union. Migration will always remain central to the contemporary human trafficking crisis, and it is vital that we learn how traffickers prey on their victims in the context of mass migration events in order to devise more effective preventions and protections.…”
mentioning
confidence: 99%